Synthesis Gas by Conversion of Methane with Carbonate Anhydride - N. I. Fayzullaev., T. B. Shoymardanov., D. R. Hamidov, B. Sh. Omanov (International Journal of Advanced Science and Technology, 2020)
The original catalyst containing (Ni2 O3 )x *(Co2 O3 )y *(ZrO2 )z *(B2 O3 )k /Al2 O3 , characterized by a decrease in the degree of coking to carry out the carbonate conversion reaction of methane in the study selected. Various factors ( ratio of CO 2 : CH 4 ratio, temperature, starting volumetric velocities and other factors, target product yield, process conversion and selectivity, as well as the effect of different promoters on catalyst activity in the presence of the selected catalyst in the methane carbonate conversion reaction rate) studied.